Training Model Development Film Script Writing Skills - Sudrajat, Yayan; Sari, Ni Wayan Ayu Permata; Rahmi, Dila Febriyana (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2025)
This research aims to develop and test the effectiveness of film script writing skills training to increase participants' competence in creating creative scenarios that comply with industry standards. The research method used is research and development (R&D) with the name ADE training model, a combination of the KEMP (learner analysis) model and the ADDIE (Design, Development, Implementation, Evaluation) model. The research test subjects Consists of 7 training participants, who were selected using purposive sampling. Data collection was carried out through pre-test and post-test, observation, and participant satisfaction questionnaires. Data analysis used Paired Sample T-Test. The statistical test results showed an increase in the average score from 55.43 to 78.43, with a t value = -19.63 and p-value = 0.000 (p < 0.05). These findings Shown that the training developed significantly improved participants' skills in writing movie scripts, both in terms of story structure, character development and creativity.